Amdahl's Law for Tail Latency. - DELIMITROU, CHRISTINA; KOZYRAKIS, CHRISTOS (Communications of the ACM, 2018)
The article discusses the implications of Amdahl's law for tail latency and its consequences for parallel processing and single-thread performance optimization for data-center hardware development and software architecture design. The alleged importance of balancing memory resource usage and computational resources is described along with the implications of queuing theory for hardware design.